2013
DOI: 10.6061/clinics/2013(12)09
|View full text |Cite
|
Sign up to set email alerts
|

The putative role of ovary removal and progesterone when considering the effect of formaldehyde exposure on lung inflammation induced by ovalbumin

Abstract: OBJECTIVE:Formaldehyde exposure during the menstrual cycle is known to affect the course of allergic lung inflammation. Because our previous data demonstrated that formaldehyde combined with an ovariectomy reduced allergic lung inflammation, we investigated the putative role of ovary removal and progesterone treatment when considering the effect of formaldehyde on allergic lung inflammation.METHOD:Ovariectomized rats and their matched controls were exposed to formaldehyde (1%, 3 days, 90 min/day) or vehicle, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…Formaldehyde (FA) is a pollutant widely employed in several industries and also in anatomy, pathology and histology laboratories. Studies have shown the correlation between exposure to FA and development or worsening of asthma [1] , [2] , [3] , [4] , [5] , [6] . In addition, FA exposure during the pregnancy causes changes in the immune system of offspring, culminating to impaired defenses against infectious or allergic stimulus by fetal programming mechanisms [7] , [8] .…”
Section: Introductionmentioning
confidence: 99%
“…Formaldehyde (FA) is a pollutant widely employed in several industries and also in anatomy, pathology and histology laboratories. Studies have shown the correlation between exposure to FA and development or worsening of asthma [1] , [2] , [3] , [4] , [5] , [6] . In addition, FA exposure during the pregnancy causes changes in the immune system of offspring, culminating to impaired defenses against infectious or allergic stimulus by fetal programming mechanisms [7] , [8] .…”
Section: Introductionmentioning
confidence: 99%